Improving Understanding of the Birth Process of the Umayyad Dynasty Thru the Application of Storytelling Method in Class X-1 MA - Abul Fidan Tahalu; Herson Anwar; Habibie Yusuf; Tuharso (Global Action and Education for Society, 2026)
This study aimed to improve students' understanding of The Emergence of the Umayyad Dynasty through the implementation of the storytelling method in Class X-1 of MA Al-Islam Telaga Biru, Gorontalo Regency. This research employed a Classroom Action Research (CAR) design conducted in two cycles. The participants were 25 students. Data were collected through observation, tests, interviews, and documentation. The results showed that the storytelling method improved students’ understanding, as indicated by the increase in the average score from 60 in the pre-action stage to 65 in Cycle I and 78 in Cycle II. In addition, students’ learning activities also improved during the learning process. Therefore, the storytelling method was effective in improving students’ understanding of The Emergence of the Umayyad Dynasty.